HEALTH, A STRATEGIC NATIONAL RESOURCE - ȘTEFĂNESCU, Alexandru Mihai; MIHOREANU, Larisa; ȘTEFĂNESCU, Alexandra Rodica (Annals of Spiru Haret University. Economic Series, 2019)
Health has always been the most valuable and beautiful gift that Nature offered to humans. Unfortunately, nowadays, people value and desire more wealth than health; often they remain indifferent to the degradation of their own health. Only in front of serious diagnoses people start appreciating their true wealth – the health. The allopathic medicine has no giants’ power, as it sometimes treats symptoms and diseases instead of illnesses’ fundamental causes. Education, the other field revealing the horizon of knowledge, provides creative alternatives for spending revenues in favour of healthy individuals and societal robust development. The purpose almost remains the same: use both complex potentials and opportunities to increase motivation, accomplish joy of life and fulfil desires to build wellbeing. The link between Health and Education has complex links and hidden mechanisms waiting for to be explored and used in favour of all.